Pengaruh Job description dan Motivasi Pegawai Terhadap Produktivitas Kerja Pegawai Pada Dinas Sumber Daya Air dan Bina Marga Kota Surabaya - Ardianto, Bagus Putra; Siswanto, Siswanto; Ernawati, Ernawati; Hidayat, Arif (Universitas Pahlawan Tuanku Tambusai, 2024)
Problems that still hamper employee productivity and can hinder the achievement of Surabaya Hebat's vision are Infrastructure and Transportation. Infrastructure issues that are not yet optimal, including inefficient public transportation, can affect employee mobility and hamper their performance. The suboptimal quality of public services, such as slow bureaucratic processes, can hinder employees' work efficiency and productivity. This study aims to determine the influence of Job description factors and employee motivation on employee work productivity at the Surabaya City Water Resources and Bina Marga Office. The results showed that Job description and employee motivation had a significant effect simultaneously on employee productivity at the Surabaya City Water Resources and Bina Marga Office. Job description and employee motivation have a significant effect partially on employee productivity at the Surabaya City Water Resources and Highways Agency.